Curvature‐induced Zn 3d Electron Return on Zn−N4 Single‐atom Carbon Nanofibers for Boosting Electroreduction of CO2. Issue 2 (23rd November 2020) - Fang, Mingwei; Wang, Xingpu; Li, Xueyan; Zhu, Ying; Xiao, Guozheng; Feng, Jingjing; Jiang, Xiaohui; Lv, Kuilin; Zhu, Ying; Lin, Wen‐Feng
Abstract: The electrochemical CO2 reduction to desired chemical feedstocks is of importance, yet it is still challenging to obtain high production selectivity with low overpotential at a current density surpassing the industry benchmark of 100 mA cm −2 . Herein, we constructed a low‐cost Zn single‐atom anchored on curved N‐doped carbon nanofibers (Zn SAs/N−C) by a facile noncovalent self‐assembly approach. At a low overpotential of only 330 mV, the Zn SAs/N−C exhibited simultaneously both a high current density up to 121.5 mA cm −2 and a CO FE of 94.7 %, superior to the previous reports. Experiments and DFT calculations revealed that the Zn atoms in Zn−N4 acted as the active sites, while adjacent pyridine‐N coupled with Zn−N4 could synergistically decrease the free energy barrier for intermediate *COOH formation. Importantly, the curvature of catalyst induced Zn 3d electrons that were bound to the Zn−N bonds to return to Zn atom, thereby leading to an increase in electron density of Zn and accelerating CO2 electroreduction to CO. Abstract : Electrochemical CO2 reduction reaction : A Zn single‐atom layer anchored on N‐doped carbon nanofiber (Zn SAs/N−C) catalyst was developed by a self‐assembly method. The Zn SAs/N−C achieved both a high current density of 121.5 mA cm −2 and a CO FE of 94.7 % at a low overpotential of 330 mV. Further studies revealed that the adjacent pyridine‐N had a synergistic effect with Zn−N4 . Zn 3d electrons that bound to Zn−N bonds could return to Zn atom by a curvature‐induced electron transfer.